An exploratory study on online social network marketing in the Singapore travel agent industry. - Chan, Shu Ling. (2009)
The travel agent industry is a crucial, if not often overlooked, component of Singapore’s travel industry. The advent of Web 2.0 technologies has allowed their travel suppliers to market their products independently online, diminishing the traditional role of travel agents as middle-men. Regrettably, despite the presence of viable marketing tools, local travel agents have been slow to adopt online social network marketing (OSNM).